Aberrant orbitofrontal connectivity in marijuana smoking adolescents - Melissa Patricia Lopez-Larson; Jadwiga Rogowska; Deborah Yurgelun-Todd (Developmental Cognitive Neuroscience, 2015)
Introduction: Orbitofrontal (OFC) circuits have been implicated in the pathophysiology of substance use disorders. The current study examined OFC functional connectivity differences in marijuana-using adolescents (MJ) and non-using healthy controls (HC). Methods: Functional magnetic resonance imaging (fMRI) resting-state data were obtained on a 3 T MRI scanner on 31 HC and 43 heavy MJ smokers. Image analyses were performed between groups (MJ, HC) for the left and right OFC separately. Regression analyses between OFC functional connectivity and lifetime MJ use, age of first MJ use and impulsivity also were performed. Results: Increased OFC functional connectivity to frontal and motor regions was observed in heavy MJ users compared to HC. Earlier age of first MJ use was associated with increased functional connectivity of the right OFC to motor regions. High lifetime MJ use was associated with increased OFC functional connectivity to posterior brain regions in MJ youth. Discussion: Findings indicate atypical OFC functional connectivity patterns in attentional/executive, motor and reward networks in adolescents with heavy MJ use. These anomalies may be related to suboptimal decision making capacities and increased impulsivity. Results also suggest different OFC connectivity patterns may be present in adolescents with early onset of MJ use and high lifetime exposure to MJ.